2007
DOI: 10.2337/dc07-0447
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the WHO-5 Well-Being Index in Adolescents With Type 1 Diabetes

Abstract: Index (WHO-5) is a short self-report instrument that appears suitable for this purpose. This study is the first to assess the reliability and validity of the WHO-5 in adolescents with type 1 diabetes.RESEARCH DESIGN AND METHODS -Ninety-one adolescents with type 1 diabetes (aged 13-17 years) from four pediatric clinics completed the WHO-5, along with other psychological measures: the Center for Epidemiologic Studies Depression Scale (CES-D), the Diabetes Family Conflict Scale (DFCS), and the mental health and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
201
2
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(233 citation statements)
references
References 25 publications
19
201
2
5
Order By: Relevance
“…This result was corroborated by the factor analysis, which, as in Dutch [12] and Thai [13] studies, suggested a unidimensional structure of the construct. All of the questions showed high factor loads ([0.6), with the two questions related to ''energy'' presenting the highest factor loads, followed by those related to ''depression'', ''anxiety'' and ''positive well-being''.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This result was corroborated by the factor analysis, which, as in Dutch [12] and Thai [13] studies, suggested a unidimensional structure of the construct. All of the questions showed high factor loads ([0.6), with the two questions related to ''energy'' presenting the highest factor loads, followed by those related to ''depression'', ''anxiety'' and ''positive well-being''.…”
Section: Discussionsupporting
confidence: 85%
“…A Cronbach's alpha value of 0.83 for both general and depressed samples means that all of the five questions are related to each other, yet they are not identical, and thus, none of them can be dismissed. Similar internal consistency, ranging from 0.82 to 0.89, was found in previous studies with different populations [11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 82%
“…Positive correlations between QoL and the self-esteem of young people with T1DM indicate that these concepts are related (42)(43) . The Brazilian study confirmed this finding through the application of the Quality of Life Instrument for Young People with Diabetes and the Rosenberg Self-Esteem Scale to 124 adolescents (r=0.42 to 0.59; p<0.001) (42) .…”
Section: Rev Esc Enfermmentioning
confidence: 99%
“…[5] The reliability and validity of this instrument have been proved in the screening of patients for depression in all age groups. [5][6][7][8] Compared to those without depression, medical outpatients with depressive symptoms or disorders experienced decrements in the quality of life. [9] The fi ve items in the questionnaire refl ected presence and absence of positive well-being.…”
Section: Methodsmentioning
confidence: 99%